Effective Use of Statistical in Accounting and Business (Book). - Zeff, Stephen A.; Hill, Thomas M. (The Accounting Review, 1965)
Reviews the book "Effective Use of Statistics in Accounting and Business," by John B. O'Hara and Richard C. Clelland